2020
DOI: 10.1101/2020.03.19.998567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acarbose Protects From Central and Peripheral Metabolic Imbalance Induced by Benzene Exposure

Abstract: Abbreviations:CNS, central nervous system; ARC, arcuate nucleus of the hypothalamus; DMH, dorsomedial hypothalamic nucleus; LHA, lateral hypothalamus; PVH, paraventricular hypothalamic nucleus; AbstractBenzene is a well-known human carcinogen that is one of the major components of air pollution. Sources of benzene in ambient air include cigarette smoke, e-cigarettes vaping and evaporation of benzene containing petrol processes. While carcinogenic effects of benzene exposure have been well studied, less is know… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Under these conditions, benzene exposure had no significant effect on litter size or composition and no significant changes in animals white blood cell counts (Debarba et al 2020). Our findings indicate that maternal exposure to benzene induces deleterious effects on energy expenditure, glucose metabolism, and insulin resistance in adult offspring in a sex-specific manner, providing the evidence that gestational benzene exposure is a potential risk factor for metabolic disorders.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Under these conditions, benzene exposure had no significant effect on litter size or composition and no significant changes in animals white blood cell counts (Debarba et al 2020). Our findings indicate that maternal exposure to benzene induces deleterious effects on energy expenditure, glucose metabolism, and insulin resistance in adult offspring in a sex-specific manner, providing the evidence that gestational benzene exposure is a potential risk factor for metabolic disorders.…”
Section: Introductionmentioning
confidence: 58%
“…This adapted regimen for benzene inhalation resembles chronic human benzene exposure levels in highly polluted gas stations, or exposure to tobacco smoke (De Donno et al 2018;Lorkiewicz et al 2019;Pankow et al 2017). We have recently demonstrated that under these conditions, benzene exposure has no significant changes in white blood cell counts in benzene exposed animals versus control animals breathing room air (Debarba et al 2020). Maternal exposure to benzene did not significantly affect male and female offspring body mass at weaning and throughout adulthood ( Figure 1B and C).…”
Section: Gestational Benzene Exposure Does Not Alter Body Weight In Tmentioning
confidence: 85%
See 3 more Smart Citations